Medical emergency team calls in the radiology department: patient characteristics and outcomes. Issue 6 (2nd March 2012) - Ott, Lora K; Pinsky, Michael R; Hoffman, Leslie A; Clarke, Sean P; Clark, Sunday; Ren, Dianxu; Hravnak, Marilyn
Abstract : Objective: We sought to identify the characteristics of patients who experience medical emergency team calls in the radiology department (MET-RD) and the relationship between these characteristics and patient outcomes. Design/participants: Retrospective review of 111 inpatient MET-RD calls (May 2008–April 2010). Setting: Academic medical centre with a well established MET system. Measurements: The characteristics of patients before, during and after transport to radiology were extracted from medical records and administrative databases. These characteristics were compared between patients with good and poor outcomes. Main results: The majority of patients who experience MET-RD calls had a Charlson Comorbidity Index ≥4 and were from non-intensive care units (60%). Almost half (43%) of MET-RD calls occurred during patients' first day in hospital. Patients commonly arrived with nasal cannula oxygen (38%), recent tachypnoea (28%) and tachycardia (34%). A minority (16%) fulfilled MET call criteria in the 12 h before the MET-RD. MET-RD etiologies were cardiac (41%), respiratory (29%) or neurological (25%), and occurred most frequently during CT (44%) and MRI (22%) testing. Post MET-RD, the majority of patients (70%) required a higher level of care. Death before discharge (25%) was associated with need for cardiovascular support prior to RD transport (p=0.02), need for RD monitoring (p=0.02) and need for heightened RD surveillance (p=0.04). Conclusions: The majority of patients who experienced MET-RD calls came from non-intensive care units, with comorbidities and vital sign alterations prior to arrival at the RD. Risk appeared to be increased for those requiring CT and MRI. These findings suggest that prior identification of a subset of patients at risk of instability in the RD may be possible.